Students’ Perceptions and President Buhari’s Administration (2015-2019) - Olakunle OLOWOJOLU; Bamidele RASAK; Barnabas OBASAJU; Oluwaseun OGUNDELE; Solomon Adebayo ADEDIRE (Communications of International Proceedings, 2020)
General Muhammudu Buhari (retd), a former military ruler became democratically elected president of Nigeria in 2015 after making several attempts.  Buhari’s assumption to power signaled the end of the 16 years rule of the erstwhile ruling party, the People’s Democratic Party (PDP). This study is premised upon the perceptions of undergraduate students in Landmark University on the performance of President Muhammudu Buhari’s administration. Well structured questionnaires were administered to students of Political Science, International Relations, Sociology and Economics departments. he feedbacks garnered from students reveal an overall pessimistic outlook on the performance of the incumbent administration as most of the responses of students fall in the negative domains in respect of issues appertaining national security, the state of the economy and the anti-corruption drive.
Keywords: Perceptions; President Muhammudu Buhari; National Security; Economy; Anti-corruption; Structured Questionnaires.